Review of West Indian Asyndetus Loew (Diptera: Dolichopodidae), with descriptions of five new species - Runyon, Justin B. (Zootaxa, 2026)
The species of Asyndetus Loew (Diptera: Dolichopodidae) occurring in the West Indies are reviewed and nine species are recognized, including five new species: A. ammophilus Loew, A. atratus sp. nov., A. caribeus sp. nov., A. erosicornis sp. nov., A. flabellifer sp. nov., A. fratellus Aldrich, A. interruptus (Loew), A. pogonops Robinson and A. virginensis sp. nov. An unnamed tenth species, known from females, is reported. Males of the new species have partly sclerotized, mandible-like labella, which is rare in brachyceran Diptera. Previous reports of A. syntormoides Wheeler in the West Indies are determined to be erroneous. The following new synonyms are proposed: Asyndetus deficiens Robinson = A. fratellus, syn. nov.; A. dominicensis Robinson = A. fratellus, syn. nov.; A. exiguus Van Duzee = A. fratellus, syn. nov. and A. currani Van Duzee = A. fratellus, syn. nov. The species are illustrated, distributions mapped, and a key to males is provided.